Otimização aplicada ao projeto de enrolamentos de máquinas CA - Franco, André Luiz Carneiro (2015)
This work presents an analysis and optimization metho dology for the AC machines stator windings design, based on magnetomotive force harmonic distortion study. For that, the three-phase double layer integral and fractional-slot windings are chosen. At first, magnetomotive force in conventional windings study is p erformed, comparing harmonic analysis by distortion and Fourier sp ectrum with the traditional calculation metho dology of winding factors. In relation to the metho d, the stator windings arrangement optimization using genetic algorithms is prop osed, in order to suggest alternative optimized layouts. The results are presented and discussed.